Representações de saúde e doença por profissionais da Saúde no contexto pluricultural de fronteira. - Duarte, Teresa Cristina (2014)
The biomedical model institutionally assumed in Healthcare today has been unable to achieve comprehensiveness regarding individual care. The conflict this sector is facing has required a deeper understanding of the human being, whos meaning is found in the context. Among the many challenges facing health professionals embedded in a context of borders, there is the understanding of aspects involving cultural differences and social representations, which motivated the proposition of this very research. In order to investigate how health professionals in the plurilcultural border scenario build their discursive practices, representations of health and desease, three research questions were developed: a) How the (re) meaning of the concept of health and disease and the role of interdisciplinarity in the current context representations of health and desease, three research questions were developed has been made? b) How the representations of cultural differences influence their professional practice? c) What representations are formed by health professionals on health and disease? To answer these questions a qualitative / interpretive methodological approach was followed. The generation of data for the analysis was conducted through audio-recorded semi-structured interviews with 10 participants. A field diary was also used. As categories emerged from the formulated representations regarding cultural differences and their influences in professional practices we have: cultural plural due to differences present in all relationships, the presence of practices flexibility adopted by health professionals facing the individual‟s cultural needs and the paradox between recognizing the importance of culture and the lack of it‟s effective application, indicated primarily by the biomedical model of health. The representations of health and desease by health professionals allowed to observe the acceptance of this concept as a dynamic process that is individually established with an overview divided into three categories: the relation with well-being; the dynamic process; the individual perceptions. Through the analysis it was evident that contact with people from other cultures leads to changes which, in most cases, were positive in the sense that the professional has become more open, flexible and attentive to the other, a factor that contributes to health and disease representation to be conditioned by external factors and determined by the individual.